Penggunaan Konfiks Ke-An pada Artikel Olahraga Harian Solopos dan Pemanfaatannya Sebagai Bahan Pembelajaran Bahasa Indonesia Kelas XII Akuntansi SMK Negeri 01 Banyudono - Aning, Retno Dewi, Drs. Yakub Nasucha, M.Hum (2016)
The purpose of this study was to determine: 1) Use of an konfiks all the sports articles in newspapers Solo Pos, 2) Utilization konfiks use an all in sport articles in newspapers Solo Pos towards learning Accounting class XII student of SMK Negeri 1 Banyudono. The research is a qualitative study using descriptive methods. Sources of data in this study is sports news articles that contain the use of an konfiks all the daily newspapers in October 2015 edition of Solo Pos. The data is in the form of words using an konfiks all. Data collection techniques in this study was conducted using see and note. Test the validity of the data using triangulation theory. Analysis of the data in this study using agih. Based on the results of data analysis, data found as many as 40 data is the formation of konfiks to late, the use konfiks to late in forming nouns found 1 record, use konfiks to late in forming a passive verb found 5 Data and and use konfiks to late at formation of adjectives found 14 data. The use of such an kofiks all contained in the word formation. Morphological studies related about konfiks material can be used as teaching material in SMK Negeri O1 Banyudono. Keywords: konfiks, news articles, learning